1988
DOI: 10.1002/1097-0142(19881001)62:7<1389::aid-cncr2820620725>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Breast self-examination and survival from breast cancer

Abstract: The relationship between breast self-examination (BSE) and survival was evaluated in 2093 women with breast cancer newly diagnosed between June 1975 and February 1979. In this population self-examiners were younger, more educated, and more likely to be white, premenopausal, and married than nonexaminers. Self-examiners also tended to seek medical care more rapidly and to have earlier stages of disease at diagnosis. Five years after diagnosis, the cumulative observed survival rates from breast cancer were 76.7%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(41 citation statements)
references
References 18 publications
3
38
0
Order By: Relevance
“…Several studies have shown that various characteristics that are likely to be associated with dying from breast cancer were also associated with BSE practice, but analyses adjusting for the potential effect of such confounding on mortality were not reported. Women who practised BSE tended to be younger, premenopausal and of a higher socioeconomic status (Smith et al, 1980;Feldman et al, 1981;Tamburini et al, 1981;Huguley et al, 1988;Le Geyte et al, 1992;Auvinen et al, 1996). Much of the reduction in mortality observed in these studies might therefore be explained by a combination of these and other confounding factors as well as the aforementioned biases, rather than a real effect of BSE.…”
Section: Discussion Women Who Practise Bsementioning
confidence: 88%
See 4 more Smart Citations
“…Several studies have shown that various characteristics that are likely to be associated with dying from breast cancer were also associated with BSE practice, but analyses adjusting for the potential effect of such confounding on mortality were not reported. Women who practised BSE tended to be younger, premenopausal and of a higher socioeconomic status (Smith et al, 1980;Feldman et al, 1981;Tamburini et al, 1981;Huguley et al, 1988;Le Geyte et al, 1992;Auvinen et al, 1996). Much of the reduction in mortality observed in these studies might therefore be explained by a combination of these and other confounding factors as well as the aforementioned biases, rather than a real effect of BSE.…”
Section: Discussion Women Who Practise Bsementioning
confidence: 88%
“…Relative risk of having advanced breast cancer in BSE vs non-BSE groups Practise BSE vs do not practise BSE Foster, 1984Huguley, 1988Kurebayashi, 1994 All All Koibuchi, 1998Kuroishi, 1992Greenwald, 1978Owen, 1985Ogawa, 1987Tamburini, 1981Feldman, 1981Smith, 1985Smith, 1980 Cancer found by BSE vs found by chance 0.60 (0.46 −0.80) 0.66 (0.44 −1.01) Figure 2 Observational studies of women with breast cancer, comparing the rates of advanced breast cancer between the BSE and non-BSE groups. A test for heterogeneity between the studies yielded a P-value of o0.001 for those studies based on women who practise BSE and a P-value of 0.051 for those based on finding cancer by BSE.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations